1988
DOI: 10.1016/0093-934x(88)90123-x
|View full text |Cite
|
Sign up to set email alerts
|

A linguistic deficit resulting from right-hemisphere damage

Abstract: The ability of right-brain-damaged (RBD) subjects to correctly insert a word into a well-formed stimulus sentence was tested. Subjects also performed three evaluative tasks designed to establish their degree of general cognitive impairment. The performance of RBD subjects on these tasks was compared to that of left-brain-damaged (LBD) and non-brain-damaged (NBD) subjects. Although RBD subjects outperformed LBD subjects on the language-related evaluative tasks, the RBD group was significantly more impaired on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
3
24
0
3
Order By: Relevance
“…As noted by the authors, such a finding suggests that RBD patients may simply have more difficulty than normals in rejecting an initial interpretation. This inability of RBD individuals to reject contradictory elements has been observed previously (Wapner et al, 1981) and appears to parailel apparent sentence processing deficits observed by Schneiderman and Saddy (1988) who found that RBD individuals had difficulty reassigning the syntactic status of a word, as weil as the results of Ulatowska and Baker (1976) who found that RBD patients had difficulty rearranging words in an anagram task to forrn a different correct arrangement, once a fust solution was found.…”
Section: • • •mentioning
confidence: 64%
See 3 more Smart Citations
“…As noted by the authors, such a finding suggests that RBD patients may simply have more difficulty than normals in rejecting an initial interpretation. This inability of RBD individuals to reject contradictory elements has been observed previously (Wapner et al, 1981) and appears to parailel apparent sentence processing deficits observed by Schneiderman and Saddy (1988) who found that RBD individuals had difficulty reassigning the syntactic status of a word, as weil as the results of Ulatowska and Baker (1976) who found that RBD patients had difficulty rearranging words in an anagram task to forrn a different correct arrangement, once a fust solution was found.…”
Section: • • •mentioning
confidence: 64%
“…Another interesting finding that emerged from the results of this experiment concemed the daim that RBD individuals have difficulty revising initial interpretations (e.g. Brownell et al, 1986;Schneiderman & Saddy, 1988;Ulatowska & Baker, 1976). In facto the results ofthis experiment suggested otherwise, at least with respect to the factor of implicit causality.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Schneidermann e Saddy (1988) in uno studio su pazienti destro-lesi rilevano che questi soggetti sembrano avere minore flessibilità nell'attribuzione di proprietà strutturali agli enunciati. Il test prevedeva l'interpretazione dell'enunciato "the boy hit the man with the cane" in questo caso "con la canna" può essere un'espressione qualificativa che descrive l'uomo colpito o un'espressione strumentale che precisa il modo in cui il ragazzo ha colpito l'uomo: i pazienti esaminati da Schneidermann e Saddy non riescono a vedere queste due possibilità interpretative.…”
Section:  Dominanza Emisfericaunclassified